A Mouse Model of Autoimmune Cholangitis via Syngeneic Bile Duct Protein Immunization. Issue 1 (December 2017) - Ma, Wen-Tao; Liu, Qing-Zhi; Yang, Jing-Bo; Yang, Yan-Qing; Zhao, Zhi-Bin; Ma, Hong-Di; Gershwin, M.; Lian, Zhe-Xiong
Abstract Primary biliary cholangitis (PBC) is an autoimmune liver disease characterized by the destruction of interlobular biliary ductules, which progressively leads to cholestasis, hepatic fibrosis, cirrhosis, and eventually liver failure. Several mouse models have been used to clarify the pathogenesis of PBC and are generally considered reflective of an autoimmune cholangitis. Most models focus on issues of molecular mimicry between the E2 subunit of the pyruvate dehydrogenase complex (PDC-E2), the major mitochondrial autoantigen of PBC and xenobiotic cross reactive chemicals. None have focused on the classic models of breaking tolerance, namely immunization with self-tissue. Here, we report a novel mouse model of autoimmune cholangitis via immunization with syngeneic bile duct protein (BDP). Our results demonstrate that syngeneic bile duct antigens efficiently break immune tolerance of recipient mice, capturing several key features of PBC, including liver-specific inflammation focused on portal tract areas, increased number and activation state of CD4 and CD8 T cells in the liver and spleen. Furthermore, the germinal center (GC) responses in the spleen were more enhanced in our mouse model. Finally, these mice were 100% positive for anti-mitochondrial antibodies (AMAs). In conclusion, we developed a novel mouse model of PBC that may help to elucidate the detailed mechanism of this complex disease.